New palynological and isotopic data for the Triassic of the western Cantabrian Mountains (Spain) - Barrón, E.; Sánchez-moya, Y.; Sopeña, A. (Journal of Iberian Geology, 2009)
Triassic carbonate rocks of the western Cantabrian Mountains, northern Spain, have long been attributed to the Muschelkalk facies, and as such have been correlated with other Middle Triassic carbonate units of the Iberian Peninsula. Data on palynological assemblages here presented, point to a Ladinian-lower Carnian age of the upper part of the Buntsandstein facies in this area. In addition, the 87Sr/86Sr ratio of the limestones formerly attributed to the Muschelkalk facies indicates a Norian or Norian-Rhaetian boundary age. These findings also imply that the position of the marine coast during the Middle Triassic Tethys transgression should be moved to a more easterly position, in the Basque Country.